Obstetricians and gynecologists: Which characteristics do Israeli lesbians prefer?. Issue 2 (17th September 2014) - Amir, Hadar; Gophen, Ruth; Amir Levy, Yifat; Hasson, Joseph; Gordon, David; Amit, Ami; Azem, Foad
Abstract Aim The aim of this study was to explore lesbians' preferences when choosing obstetricians/gynecologists. Material and Methods This cross‐sectional study included 100 lesbian and 100 heterosexual women. A 40‐item questionnaire assessed the correlation between a patient's sexual identity and her specific preferences for obstetricians/gynecologists. Results The top five most important parameters for both groups in choosing obstetricians/gynecologists overlapped greatly. Four of those were experience, ability, knowledge and personality. Only one parameter differed: lesbians ranked 'sexually tolerant' as the third most important characteristic while heterosexuals ranked 'availability' as the fifth most important characteristic. Lesbians rated 'sexual tolerance' significantly higher than heterosexuals (P < 0.001). More lesbians (56%) preferred female obstetricians/gynecologists compared to heterosexuals (21%) (P < 0.001). When compared to heterosexuals, more lesbians preferred female obstetricians/gynecologists for intimate and non‐intimate procedures (P < 0.001). But within the lesbian population, a higher percentage of subjects showed a preference for female obstetricians/gynecologists only for intimate procedures. Lesbians used the following to describe their preference for female obstetricians/gynecologists: feeling more comfortable; gentle; sympathetic; patient; more understanding of women's health; better physicians in general; and more sexually tolerant (P < 0.001 vs heterosexual). However, when we looked only at the lesbian population, the majority did not exhibit a preference for a female obstetrician/gynecologist for any of these reasons. The main reason given by the 56% of the lesbians who said they prefer female obstetricians/gynecologists was feeling more comfortable. Conclusion Overwhelmingly lesbians prefer sexually tolerant obstetricians/gynecologists regardless of their gender; however, only a small number of lesbian subjects in this study considered their obstetricians/gynecologists as displaying this characteristic.